2009
DOI: 10.1002/mus.21180
|View full text |Cite
|
Sign up to set email alerts
|

Needle electromyography

Abstract: Physiologic assessment of diseases of the motor unit from the anterior horn cells to the muscles relies on a combination of needle electromyography (EMG) and nerve conduction studies (NCS). Both require a unique combination of knowledge of peripheral nervous system anatomy, physiology, pathophysiology, diseases, techniques, and electricity is necessary. Successful, high-quality, reproducible EMG depends on the skills of a clinician in patient interaction during the physical insertion and movement of the needle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
192
0
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(202 citation statements)
references
References 53 publications
2
192
0
8
Order By: Relevance
“…In standard needle EMG a needle electrode is inserted into the muscle [10], from which electrical activity in multiple motor units (groups of muscle fibres innervated by a single nerve fibre) is sampled. Commonly a concentric needle electrode is used-a hollow needle containing an insulated wire with a bevelled tip resulting in a recording area in the region of 125 9 580 lm.…”
Section: Standard Needle Emgmentioning
confidence: 99%
“…In standard needle EMG a needle electrode is inserted into the muscle [10], from which electrical activity in multiple motor units (groups of muscle fibres innervated by a single nerve fibre) is sampled. Commonly a concentric needle electrode is used-a hollow needle containing an insulated wire with a bevelled tip resulting in a recording area in the region of 125 9 580 lm.…”
Section: Standard Needle Emgmentioning
confidence: 99%
“…14,23,34 Electrodiagnostic (EDX) testing, consisting of needle electromyography (EMG) and nerve conduction studies, is used to evaluate the integrity of the neuromuscular system, including upper and lower motor neurons, the neuromuscular junction, and skeletal muscle. 11,14,22,23,31 Conducted as an extension of the clinical examination, EDX testing is the primary method used to objectively measure and document pathological changes or injury to the neuromuscular system, including proximally located spinal nerve roots. 11,14,22,23,31 Clinicians employ EDX testing to evaluate patients with sciatica, 14,23,27 with particular emphasis on the results of the needle EMG examination, which has high diagnostic specificity in these patients.…”
Section: T T Conclusionmentioning
confidence: 99%
“…11,14,22,23,31 Conducted as an extension of the clinical examination, EDX testing is the primary method used to objectively measure and document pathological changes or injury to the neuromuscular system, including proximally located spinal nerve roots. 11,14,22,23,31 Clinicians employ EDX testing to evaluate patients with sciatica, 14,23,27 with particular emphasis on the results of the needle EMG examination, which has high diagnostic specificity in these patients. 9,14,23,31 Research has demonstrated the relationship between some patient history and physical examination findings in patients with sciatica and the presence of disc herniation or nerve root impingement on diagnostic imaging.…”
Section: T T Conclusionmentioning
confidence: 99%
See 2 more Smart Citations